Haroldo de Campos, the tradition and his precursors. Some points of contact with Octavio Paz - Rivera, Jorgelina [UNESP] (Univ Estadual Paulista-unesp, 2018)
The aim is to define the haroldian synchronic poetics by means of its precursors that architect it. We use as a starting point the borgean latency that exists in Haroldo de Campos and exerts a great influence on the course and development of his literary project. His poetic work is then defined in relation to renowned authors such as Octavio Paz and Umberto Eco. The study draws heavily on the book Los hijos del limo (1974), a fundamental theoretical work of the twentieth century. From the theoretical trajectories, it is believed that Harold's writing could be called, as Monegal says, a poetics of reading (1980) because of the importance of reviving in his works his ancestors, precursor writers who form part of the writer's life experience. Through these, Campos will develop his works, and will take back these ancestors, making them part of his present in a creative game of invention.
Keywords: Haroldo de Campos; Octavio Paz; Open Literary Work; Precursors; Tradition